2008
DOI: 10.1007/s11103-008-9357-x
|View full text |Cite
|
Sign up to set email alerts
|

Two cysteine proteinase inhibitors from Arabidopsis thaliana, AtCYSa and AtCYSb, increasing the salt, drought, oxidation and cold tolerance

Abstract: Two cysteine proteinase inhibitors (cystatins) from Arabidopsis thaliana, designated AtCYSa and AtCYSb, were characterized. Recombinant GST-AtCYSa and GST-AtCYSb were expressed in Escherichia coli and purified. They inhibit the catalytic activity of papain, which is generally taken as evidence for cysteine proteinase inhibitor function. Northern blot analyses showed that the expressions of AtCYSa and AtCYSb gene in Arabidopsis cells and seedlings were strongly induced by multiple abiotic stresses from high sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
146
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(155 citation statements)
references
References 55 publications
6
146
0
3
Order By: Relevance
“…Inhibitor-CYSB is a cysteine protease inhibitor (41,42). Its interaction with BZR1 was further confirmed through an in vitro pull-down assay (Fig.…”
Section: Bzr1 Interacts With a Cysteine Proteasementioning
confidence: 78%
See 1 more Smart Citation
“…Inhibitor-CYSB is a cysteine protease inhibitor (41,42). Its interaction with BZR1 was further confirmed through an in vitro pull-down assay (Fig.…”
Section: Bzr1 Interacts With a Cysteine Proteasementioning
confidence: 78%
“…Whether CYSB acts downstream of BZR1 remains to be tested. It was reported that CYSB overexpression increases plant tolerance to abiotic stress (41,42). Whether the increase in tolerance is related to BZR1 and whether the CYSB-BZR1 interaction is functional under conditions of stress requires further evaluation.…”
Section: Functional Proteomics Is An Effective Approach For Identifyimentioning
confidence: 99%
“…Phytocystatins belong to a superfamily of Cys proteases widely distributed among eukaryotes. Plant cystatins have well-documented roles in developmental processes and biotic and abiotic stresses (Gaddour et al, 2001;Zhang et al, 2008;Hwang et al, 2010). Root expression of CYS2 was confined to the root tip, representing the first root/soil contact point.…”
Section: Differentially Expressed Proteins Reveal New Aspects Of the mentioning
confidence: 99%
“…Altogether, these data provide evidence that HY5 has an important function in regulating cold-induced gene expression. Several HY5-regulated cold-inducible genes, including those validated by qPCR, are related to cold acclimation (18)(19)(20)(21), suggesting that HY5 may also have a role in this adaptive response.…”
Section: Resultsmentioning
confidence: 99%